Antidiabetic and antioxidant evaluations of Averrhoa bilimbi L. - Ahmed, Qamar Uddin; Mat So'ad, Siti Zaiton (2018)
This research work deals with the antidiabetic and antioxidant evaluations of Averrhoa bilimbi L. and understanding its mechanism of action as an antidiabetic agent. A. bilimbi leaves are used in folk medicine for treatment of different diseases including diabetes. The present study investigates the antiradical and xanthine oxidase inhibitory activity of A. bilimbi leaves. Crude methanol extract and fractions of A. bilimbi leaves were evaluated for DPPH radical scavenging effect and xanthine oxidase inhibitory activity, and the active constituents were identified by LC-MS-QTOF analysis as well as molecular docking. The n-butanol fraction of A. bilimbi extract displayed significant DPPH radical scavenging effect with IC50 (4.14 ± 0.21μg/mL) (P<0.01) as well as xanthine oxidase inhibitory activity with IC50 (64.84 ± 3.93 μg/mL) (P<0.05). Afzelechin 3-O-alpha-L-rhamnopyranoside and cucumerin A were identified through LC-MS-QTOF and molecular docking as possible metabolites that contribute to the antioxidant activity of the n-butanol fraction. Results of this study provide a chemical lead for the synthesis of new derivatives which might prove to be potential novel therapeutic agents in the treatment of diabetes.